Analisis kesulitan membaca permulaan beserta faktor yang mempengaruhi pada peserta didik kelas I sekolah dasar - Aisyah Fahma Risqi; Rukayah Rukayah; Sandra Bayu Kurniawan (Universitas Sebelas Maret, 2024)
Abstract. This research was conducted to: (1) describe the difficulties of beginning reading and (2) describe the factors that influence the difficulties of beginning reading. This research used qualitative method with descriptive approach. Researcher use students, teacher, and parents as a resource of the data in this research. The subjects in this research were 10 students who had early reading difficulty. Data in this research were collected using observation, interview, and documentation techniques. The results found in this research include the following. First, the difficulties in beginning reading experienced by first grade students of Kampung Sewu elementary school consist of: (1) difficulty reading words as much as 38.62%, (2) difficulty reading syllables as much as 24.89%, (3) difficulty reading fluently and understanding the content of reading as much as 16.3%, (4) difficulty listening as much as 15.02%, and (5) difficulty identifying consonant letters as much as 5.15%. Second, the factors that can cause difficulties in beginning reading in first grade students of Kampung Sewu elementary school are: (1) low interest, (2) lack of motivation, (3) low intelligence levels, (4) family background, (5) lack of parental role, and (6) social and economic conditions of the living environment.